The production deployment of IPv6 on WLCG. Issue 5 (December 2015) - Bernier, J; Campana, S; Chadwick, K; Chudoba, J; Dewhurst, A; Eliáš, M; Fayer, S; Finnern, T; Grigoras, C; Hartmann, T; Hoeft, B; Idiculla, T; et al.
Abstract: The world is rapidly running out of IPv4 addresses; the number of IPv6 end systems connected to the internet is increasing; WLCG and the LHC experiments may soon have access to worker nodes and/or virtual machines (VMs) possessing only an IPv6 routable address. The HEPiX IPv6 Working Group has been investigating, testing and planning for dual-stack services on WLCG for several years. Following feedback from our working group, many of the storage technologies in use on WLCG have recently been made IPv6-capable. This paper presents the IPv6 requirements, tests and plans of the LHC experiments together with the tests performed on the group's IPv6 test-bed. This is primarily aimed at IPv6-only worker nodes or VMs accessing several different implementations of a global dual-stack federated storage service. Finally the plans for deployment of production dual-stack WLCG services are presented.